The economics of livestock disease insurance [ concepts, issues and international case studies - Koontz, Stephen R. (CABI, 2006)
This book on the economics of livestock disease insurance is organized into three major parts. Following an introduction (chapters 1-2), part II (chapters 3-8) includes a variety of discussions about what is known about how to build a livestock insuranc programme. It begins with a look at the conceptual basis for government involvement in the management of livestock diseases, including prevention, control, regulation and eradication. This discussion is picked up by looking at incentive compatibility and insurability conditions in the private sector, emphasizing how livestock disease management is unique. Compensation is also examined, including what losses should be compensated, choosing a method to value the losses, determining the portion of losses to compensate, and outlining a potential role for insurance. Finally, the complexity of the risks at the farm level is demonstrated using a model that evaluates revenue insurance. Part III (chapters 9-20) offers a diverse discussion about disease management issues and programmes in Australia, Canada, Europe and the USA. These chapters include more discussion about how to build economically sound insurance programmes, and observations are based on modelling or observing case studies. The book has a subject index